2-(2, 5-Dimethoxy-4-methylphenyl)-N-(2-methoxybenzyl)ethanamine (25D-NBOMe) and N-(2-methoxybenzyl)-2, 5-dimethoxy-4-chlorophenethylamine (25C-NBOMe) induce adverse cardiac effects in vitro and in vivo. (April 2019) - Yoon, Kyung Sik; Yun, Jaesuk; Kim, Young-Hoon; Shin, Jisoon; Kim, Sung Jin; Seo, Jung-Wook; Hyun, Sung-Ae; Suh, Soo Kyung; Cha, Hye Jin
Highlights: 25D-NBOMe and 25C-NBOMe prolonged QT intervals. 25D-NBOMe inhibited potassium channels in the hERG assay. 25D-NBOMe and 25C-NBOMe down-regulated PAK1. Abstract: Two emerging psychoactive substances, 2-(2, 5-dimethoxy-4-methylphenyl)- N -(2-methoxybenzyl)ethanamine (25D-NBOMe) and N -(2-methoxybenzyl)-2, 5-dimethoxy-4-chlorophenethylamine (25C-NBOMe), are being abused, leading to fatal and non-fatal intoxications. However, most of their adverse effects have been reported anecdotally. In the present study, cardiotoxicity was evaluated through 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay, rat electrocardiography (ECG), and human ether-a-go-go-related gene (hERG) assay. Expression levels of p21 (CDC42/RAC)-activated kinase 1 (PAK1), one of known biomarkers for cardiotoxicity, were also analyzed. Both 25D-NBOMe and 25C-NBOMe at 100 μM reduced cell viability in MTT assay. At 2.0 mg/kg and 0.75 mg/kg, they prolonged QT intervals in rat ECG. PAK1 was down-regulated by treatment with these two test compounds. Furthermore, potassium channels were inhibited by 25D-NBOMe treatment in hERG assay. Taken together, these results suggest that both 25D-NBOMe and 25C-NBOMe have potential cardiotoxicity, especially regarding cardiac rhythm. Further studies are needed to confirm the relationship between PAK1 down-regulation and cardiotoxicity.